2021
DOI: 10.4028/www.scientific.net/msf.1028.204
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Diffusion Rate of the Charge Carrier Transport in Regio-Random and Regio-Regular P3HT

Abstract: Muon spin relaxation experiment has been conducted to probe the hopping mechanism in the poly(3-hexylthiophene-2,5-diyl) (P3HT) for both types of regio-random (Rdm) and regio-regular (RR). In this study we have performed calculations over the collected data to obtain the parallel and perpendicular diffusion rates, at temperatures of 10 K and 300 K. The calculation is based on the fitting method to the empirical function that relates the relaxation rate with the diffusion rates. For Rdm-P3HT, we have obtained t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…These results are consistent with our proposed model regarding the change in dimensionality obtained from the H LF dependence of λ 1 as described in Figure 4. When comparing the diffusion rate with that for regio-regular P3HT without ZnO nanoparticles, we found that the parallel diffusion rate in the present study was of the same order of magnitude, while the perpendicular diffusion rate was two orders of magnitude higher in the high-temperature range [32]. Moreover, compared with those of other conjugated polymers such as polyaniline (PANI), polypyridine, and polyphenylenevinylene (PPV), the parallel diffusion rates of regioregular P3HT-ZnO nanoparticles are higher by up to three orders of magnitude, and the perpendicular diffusion rates are slightly higher than those of PANI and PPV at high temperature [41,42].…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…These results are consistent with our proposed model regarding the change in dimensionality obtained from the H LF dependence of λ 1 as described in Figure 4. When comparing the diffusion rate with that for regio-regular P3HT without ZnO nanoparticles, we found that the parallel diffusion rate in the present study was of the same order of magnitude, while the perpendicular diffusion rate was two orders of magnitude higher in the high-temperature range [32]. Moreover, compared with those of other conjugated polymers such as polyaniline (PANI), polypyridine, and polyphenylenevinylene (PPV), the parallel diffusion rates of regioregular P3HT-ZnO nanoparticles are higher by up to three orders of magnitude, and the perpendicular diffusion rates are slightly higher than those of PANI and PPV at high temperature [41,42].…”
Section: Resultssupporting
confidence: 52%
“…where ω = γH, γ are gyromagnetic ratios, ρ is the spin density, Ω z and Ω + are geometrical factors that are related to the scalar and dipolar hyperfine coupling parameters, and f (ω) is the spectral density of the spin correlation function as previously reported for calculating the diffusion rate in polymer samples, as shown in Equation ( 5) [31][32][33].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations